Comprehensive review of the Universal Immunization Programme (UIP) - Identifying gaps and assist in formulating improvement plan for routine immunization in few states of India - Vandana Gurnani; Pritu Dhalaria; Pradeep Haldar; Mahesh Kumar Aggarwal; Prem Singh; Ayushi Agarwal; Apurva Rastogi; Amrita Kumari; Gopal Krishna Soni (Elsevier, 2021)
Introduction: Despite the concerted efforts of the central and state governments and other immunization stakeholders, full immunization rates in India remains low. This paper outlines the findings of a comprehensive review of the Universal Immunization Programme (UIP) and provide recommendations to formulate an action plan for improving routine immunization coverage. Design: A mixed-method approach was adopted to collect data under four thematic areas, namely programme implementation, vaccine logistics and cold chain, data recording and reporting system, and programme communication in five high priority states. Results obtained for indicators under each thematic area, were then divided into four categories: a) ≥90 % - good, b) 70-90%-fair, c) 50-70 % - average and d) < 50 % - poor. Setting: The review was undertaken in five high-priority states - Bihar, Madhya Pradesh, Maharashtra, Rajasthan and Uttar Pradesh. Four districts were selected base on a scoring criterion from each state. Results: The programme implementation was found average ranging from 53.6 % to 63.8 % and the mechanism of vaccine logistic and cold chain was fair ranging from 71.0 % to 79.4 % across all the states. The mechanism of data recording and reporting was poor in Madhya Pradesh (36.8 %) and Maharashtra (47.0 %) and average in the remaining three states. Programme communication needs considerable improvement. Except Madhya Pradesh (62.4 %), the communication activities were poor in the other four states. Conclusion: The methodology of the review will help in identifying critical gaps and strengths in the immunization processes and in formulating an immunization coverage improvement plan (ICIP) in the states.